1.67 Interaction between fibroblasts and T lymphocytes is needed for IL-17 secretion and Th17 differentiation requires T cell activation. (31st January 2014) - Noack, Mélissa; Thiam, N'Diémé; Miossec, Pierre
Abstract : Background and Objectives: Rheumatoid arthritis (RA) and Psoriasis are chronic inflammatory diseases, both characterised by an immune cell infiltrate, notably Th17 cells and a migration of blood derived mononuclear cells that interact with fibroblasts (synoviocytes or skin fibroblasts) and this promotes cell proliferation. In this context, the aim of our work is to study and compare the interactions between fibroblasts and peripheral blood mononuclear cells (PBMC) on cytokine production with focus on the effect of cell contact on IL-17 pathway, in order to differentiate intracellular expression from secretion of IL-17. Materials and Methods: A co-culture system with synoviocytes or skin fibroblasts and PBMC was developed. Fibroblasts were cultured overnight in 96 well plate and normal PBMC were seeded at a 1:5 ratio for 24 h, in the presence or not of activation with PHA. Transwell system was used to study cell-cell contact effect. Supernatants were collected and IL-6, IL-1β and IL-17 production measured by ELISA. Extracellular (CD3, CD4) and intracellular (IL-17) staining of PBMC was analysed by flow cytometry. Results: Interaction between synoviocytes or skin fibroblasts and PBMC was sufficient to induce IL-6 and IL-1β production. Flow cytometry analysis showed no difference in the percentage of Th17 cells in activated-PBMC alone or cultured with synoviocytes (3.21% vs. 4.70%, respectively, p = 0.42), indicating that Th17 differentiation requires only T cell activation but not cell-cell contact. Conversely IL-17 production was highly increased only in co-cultures (activated-PBMC in co-cultures (338.31 pg/ml) vs. activated-PBMC alone (26.49 pg/ml, p = 0.0002). Transwell experiments confirm that contact between fibroblasts and PBMC was critical for IL-17 secretion, as no detection was observed in transwell system. Therefore IL-17 secretion, in addition to T cell activation, requires interaction between cells. T cell activation is required to Th17 differentiation but the interaction between cells promotes IL-17 secretion. Conclusions: The interaction between PBMC and fibroblasts (synoviocytes or skin fibroblasts) alone induces IL-6 and IL-1β production. T cell activation is required for Th17 differentiation but both PBMC activation and cell interaction with fibroblasts are needed to have high IL-17 secretion. This applies in particular to the pathogenesis of RA and psoriasis.